2016
DOI: 10.7150/ijbs.16405
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin-mediated LOX expression promotes insulinoma growth in Rip1-Tag2 mice by increasing tissue stiffness

Abstract: P-selectin, a cell adhesion molecule, is an important member of the selectin family. Recent studies have shown that P-selectin deletion inhibits tumor growth in Rip1-Tag2 mice by suppressing platelet accumulation in tumor tissues. This study aimed to evaluate whether and how P-selectin affects tumor stiffness in Rip1-Tag2 mice. To explore the role of P-selectin in tissue stiffness, we demonstrated that tumor progression in Rip1-Tag2 mice was correlated with tissue stiffness using immunofluorescence and histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[ 58 , 59 ], ECM-transforming enzymes e.g. matrix metalloproteinases (MMPs) [ 60 , 61 ], lysyl oxidase (LOX) [ [62] , [63] , [64] ], transglutaminase [ 51 , 65 ] and. orchestrating topographic reconfiguration of the stroma, such as alignment of ECM fibers, amid the plethora of aforementioned activities.…”
Section: Evolution Of Differential Stiffness and Pro-metastatic Archimentioning
confidence: 99%
“…[ 58 , 59 ], ECM-transforming enzymes e.g. matrix metalloproteinases (MMPs) [ 60 , 61 ], lysyl oxidase (LOX) [ [62] , [63] , [64] ], transglutaminase [ 51 , 65 ] and. orchestrating topographic reconfiguration of the stroma, such as alignment of ECM fibers, amid the plethora of aforementioned activities.…”
Section: Evolution Of Differential Stiffness and Pro-metastatic Archimentioning
confidence: 99%
“…LOX is a secreted, copper-dependent amine oxidase and collagen cross-linker 13 . Our preliminary study showed that up-regulation of LOX expression can increase tumor stiffness, thereby promoting insulinoma growth in Rip1-Tag2 mice and that the LOX inhibitor, β-aminopropionitrile (BAPN), could inhibit tumor progression through decreasing the amount of collagen cross-links in tumors 14 .…”
Section: Introductionmentioning
confidence: 96%
“…β-aminopropionitrile (BAPN), a well-recognized inhibitor of LOX activity. Previous researches had proved that BAPN decreases tissue stiffness in mice with insulinomas 20 . The results indicated that the tumor volumes in BAPN group were significantly smaller than those in the control group (Figure 7 B, C, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%